2014
DOI: 10.7314/apjcp.2014.15.20.8783
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Quality of Life of Korean Cancer Survivors Who Return to the Workplace

Abstract: Background: Although the prevalence of cancer is increasing, it is no longer synonymous with death. The number of cancer survivors is estimated to be increasing due to development in medical treatments and social programs; cancer survivors are increasingly returning to work after long-term unemployment. Thus, we examined the quality of life (QOL) and the factors associated with return of cancer survivors to the workplace. Materials and Methods: This study was performed using the 2008 Community Health Survey ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…This result is consistent with that of previous research that showed that the lower the socioeconomic level, the lower the awareness of QoL or subjective health status (Zafar et al, 2015). Cancer survivors continue to experience difficulties due to the economic impact of reduced socioeconomic activity or problem of returning to work in addition to the burden of medical expenses in cancer treatment (Han et al, 2014). The comorbid condition and poor health status could contribute to the unemployment of cancer survivors, losing their jobs related to treatment, and discrimination in the workplace.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with that of previous research that showed that the lower the socioeconomic level, the lower the awareness of QoL or subjective health status (Zafar et al, 2015). Cancer survivors continue to experience difficulties due to the economic impact of reduced socioeconomic activity or problem of returning to work in addition to the burden of medical expenses in cancer treatment (Han et al, 2014). The comorbid condition and poor health status could contribute to the unemployment of cancer survivors, losing their jobs related to treatment, and discrimination in the workplace.…”
Section: Discussionsupporting
confidence: 92%
“…Reference variables: Male(for gender); No(for marital status); Low(for economic burden for treatment); Gastric cancer(for cancer type); Ⅰ(for stage); Op only(for type of treatment); <2 years(for time since treatment completion), *p < 0.05; **p < 0.01. symptoms are more likely to have concerns about the disease and their overall health status, as well as anxiety or depression, which could cause secondary health problems. These problems have been reported to affect expenditure in accordance with the use of medical resources and impact the economic burden throughout the cancer survivorship trajectory (Han et al, 2014). Therefore, the issue of symptoms is likely to be connected to financial difficulty, considering problems on rehabilitation in society and recovery of economic functioning.…”
Section: Discussionmentioning
confidence: 99%
“…In the sociocultural and family component, economic problems and difficulty to return to the work role prevail in the three groups of patients, findings that coincide with Han et al (30). Cancer survivors experience difficulties due to the economic impact they face because of the reduction of their socioeconomic activity or because of problems returning to work, besides the burden of health costs during treatment.…”
Section: Discussionsupporting
confidence: 71%
“…Successful RTW after cancer can be affected by employer-related factors, social support from coworkers and subjectively perceived work environment factors [22][23][24].…”
Section: Introductionmentioning
confidence: 99%